Nag Hammadi Codices (2020)
The article offers information on the Nag Hammadi Codices that are group of papyrus manuscripts discovered near the city of Nag Hammadi in southern Egypt. Topics include reports that the discovery was made in 1945 by Egyptian farmers digging for fertile soil at the base of the Jabal al-Tarif cliff on the east bank of the Nile River across from Nag Hammadi.
Keywords: Egypt; Egyptians; Farmers; Manuscripts; Nag Hammadi Codices